Synthesising graphene with renewably‑sourced bio‑carbon precursors: A brief review - Amiruddin, Hilmi; Abd Rahman, Farah Hannani; Abdollah, Mohd Fadzli; Mohd Zulkifi, Nurin Wahidah; Samion, Syahrullail; Umehara, Nortisugu; Tanemura, Masaki; Honda, Mitsuhiro; Morina, Ardian (Springer Nature, 2024)
Graphene is a 2D material with exceptional properties that surpass those of many other materials in many respects. Conventional methods of graphene synthesis heavily rely on gaseous carbon (C) precursors, primarily hydrocarbons; such as methane or ethylene; that have signifcantly negative efects on the environment. The global shift towards sustainability and eco-conscious practices has increased the need for graphene production methods that are sustainable. As such, multiple studies have explored alternative sources of C, particularly bio-based materials, as well as waste-to-value processes. Reusing bio-based materials as C-based precursors not only addresses the urgent need for C sources that are sustainable and environmentally friendly but efectively creates a circular economy in the materials science and technology industry. As such, this present study explores the methods of synthesising, applying, and optimising the conversion of bio-based renewable solid carbon (SC) and liquid carbon (LC) precursors derived from a diverse range of C sources; such as lignocellulosic biomass, agricultural residues, and everyday vegetable oils; into high-quality graphene. The fndings emphasise the promising role of renewable SC and LC precursors in the pursuit of sustainable and environmentally responsible methods of graphene production.